Revisão do instrumento de avaliação de cursos adotado pelo INEP/MEC na perspectiva da graduação na modalidade a distância - Pinheiro, Tânia Saraiva de Melo (2012)
The fast increase in the number of higher education enrollments requires new strategies do assess its quality. The current assessment policy, the National System for Assessment of Higher Education, establish external evaluative processes for institutions, courses and students. In 2006, the first instrument for external evaluation of courses was developed and frequent updates have been presented since then. This research hypothesized that the current external evaluation instrument needed to be revised to better address the complexity of distance learning courses. Its main objective is to propose improvements in the official instrument to assess high education courses, from the distance learning point of view. Four specific objectives have been established: analyze the public policies evolution in regard to its procedures and instruments; identify an educational evaluation model in accordance with the Brazilian context; identify the specific characteristics of distance learning courses not covered by the existing instrument; propose and validate a new version of the instrument used by INEP/MEC for evaluation of distance courses. The methodological approach consisted of a three-cycle incremental development, each with specific goals and research techniques. The first cycle outlined the basic framework, selecting a program evaluation model compatible with higher education assessment policies. The second searched the particular teaching conditions of distance education courses to be included in the instrument being reformulated. The final cycle validated the proposal. As a result, the data analyzed was not enough to confirm the hypothesis that the library indicators should be revised, but has corroborated the other ones, mainly related to the need of revision of faculty´s role in distance education courses. The presentation of the new set of indicators considered not only its content but also the organization of information presented in order to improve their understanding and use in distance learning courses.